2022
DOI: 10.1039/d2ta04061a
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-assisted rapid synthesis of titanium phosphate free phosphorus doped Ti3C2 MXene with boosted pseudocapacitance

Abstract: Phosphorous (P) doping is well-known for the variety of energy materials with improved energy storage performances, however, it remains rarely explored for Ti3C2 MXene. The primary bottleneck of developing P...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 91 publications
(104 reference statements)
0
22
0
Order By: Relevance
“…105 As analyzed by density functional theory (DFT) calculations, Enyashin et al reported Re doping could promote the transition of the 2H phase and finally thermodynamically stabilize the 1T-MoS 2 nanosheets. 106 Moreover, some non-metal elements like O, 107 P, 108 and S 109 are usually doped into highly conductive MXene nanosheets via substituting the lattice C or N atoms. Recently, Peng and co-workers synthesized the single-atomic Ru doped Mo 2 CT x MXene nanosheets by reaction in solution to improve the catalytic activity (Fig.…”
Section: Defect Engineering Of 2d Materialsmentioning
confidence: 99%
“…105 As analyzed by density functional theory (DFT) calculations, Enyashin et al reported Re doping could promote the transition of the 2H phase and finally thermodynamically stabilize the 1T-MoS 2 nanosheets. 106 Moreover, some non-metal elements like O, 107 P, 108 and S 109 are usually doped into highly conductive MXene nanosheets via substituting the lattice C or N atoms. Recently, Peng and co-workers synthesized the single-atomic Ru doped Mo 2 CT x MXene nanosheets by reaction in solution to improve the catalytic activity (Fig.…”
Section: Defect Engineering Of 2d Materialsmentioning
confidence: 99%
“…Typically, TMPs are synthesized by precipitation from solution, hydrothermal methods, molten salt, microwave, or mechanochemical syntheses [20][21][22][23][24][25] . Thereby, highly crystalline and/or amorphous bulk TMPs can be obtained.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19] Typically, TMPs are synthesized by precipitation from solution, hydrothermal methods, molten salt, microwave, or mechanochemical syntheses. [20][21][22][23][24][25] Thereby, highly crystalline and/or amorphous bulk TMPs can be obtained. In particular, the amorphous state is often desired, because the absence of long-range ordering in TMPs enhances their reaction kinetics compared to the crystalline equivalents.…”
mentioning
confidence: 99%
“…Typically, TMPs are synthesized by precipitation from solution, hydrothermal methods, molten salt, microwave, or mechanochemical syntheses [15][16][17][18][19][20] Thereby, highly crystalline and/or amorphous bulk TMPs can be obtained. In particular, the amorphous state is often desired, because the absence of long-range ordering in amorphous TMPs enhances their reaction kinetics compared to the crystalline equivalents 21,22 .…”
Section: Introductionmentioning
confidence: 99%